The Impact of the Central Bank of Turkey’s Monetary Policies on Cryptocurrency Market Dynamics: An ARDL Model for 2014–2025 Period - Nazari, Azatullah; Yilmaz, Ilkay; Rad, Sevgi Tüzün (Theoretical and Practical Research in Economic Fields, 2026)
This study examines the dynamic relationship between cryptocurrency markets and monetary policy in Turkey, focusing on how macroeconomic and financial variables shape four key dimensions of the market: price, trading volume, volatility, and return. Using monthly data from 2013M09 to 2025M03, the analysis applies the Autoregressive Distributed Lag (ARDL) bounds testing approach to identify both short- and long-run relationships, complemented by Error Correction Models (ECM) to estimate adjustment speeds toward equilibrium. The findings reveal robust cointegration across all models, confirming that Turkey’s crypto market is closely linked to national and global macro-financial conditions. Exchange rate depreciation and the global bitcoin price emerge as the main long-run drivers of prices and trading volumes, while domestic policy instruments such as the policy rate and reserve requirements exert only indirect influence. In the short run, cryptocurrency returns exhibit strong momentum effects and overshooting behavior, whereas volatility shows a clear mean-reverting pattern. The results reveal that while the traditional interest rate channel of monetary policy shows no significant long-run direct impact, the liquidity channel operating through the Reserve Requirement Ratio (RRR) and Broad Money Supply (M2) remains an active and direct transmission mechanism, particularly affecting trading volumes and short-run price dynamics. The study contributes to the growing literature on monetary transmission in digital asset markets by providing country-specific evidence from an emerging economy, offering insights for both policymakers and investors on the integration of cryptocurrencies within broader financial systems.